Periorbital cellulits – a mistaken diagnosis!. (18th August 2011) - Fozard, Julia; Pandya, Nikila; Pulikot, Ashok; Fish, David; Malhotra, Raman; Lake, Damian
Abstract : A 12-year-old girl presented with a 1 week history of orbital swelling associated with granuloma, purulent discharge from the eye and preauricular and submandibular lymphadenopathy. Initial conventional treatment for presumed preseptal cellulitis was unsuccessful. Despite treatment with broad spectrum antibiotics, the preseptal cellulitis progressed to orbital cellulitis with restriction of eye movements in addition to the marked conjunctival chemosis and haemorrhage. A detailed history revealed she had been in close contact with newborn kittens at home and biopsy of the granuloma demonstrated Bartonella species, confirming the diagnosis of cat scratch disease. The child received a course of appropriate oral and topical antibiotics and steroids. Unfortunately eyesight in the right eye remains poor on follow-up.